Advances in Hydrologic Forecasts and Water Resources Management - Chang, Fi-John; Guo, Shenglian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collected recent studies on the latest methodological and operational advances in hydrological forecasting. Specifically, the collection of papers covers a range of topics related to improving hydrological forecasting via new datasets and innovative approaches.